Persistent activation of interlinked type 2 airway epithelial gene networks in sputum-derived cells from aeroallergen-sensitized symptomatic asthmatics - Jones, A.; Troy, N.; White, E.; Hollams, E.; Gout, A.; Ling, K.; Kicic, A.; Stick, S.; Sly, P.; Holt, P.; Hall, Graham; Bosco, A. (Nature Publishing Group, 2018)
© 2018 The Author(s). Atopic asthma is a persistent disease characterized by intermittent wheeze and progressive loss of lung function. The disease is thought to be driven primarily by chronic aeroallergen-induced type 2-associated inflammation. However, the vast majority of atopics do not develop asthma despite ongoing aeroallergen exposure, suggesting additional mechanisms operate in conjunction with type 2 immunity to drive asthma pathogenesis. We employed RNA-Seq profiling of sputum-derived cells to identify gene networks operative at baseline in house dust mite-sensitized (HDM S ) subjects with/without wheezing history that are characteristic of the ongoing asthmatic state. The expression of type 2 effectors (IL-5, IL-13) was equivalent in both cohorts of subjects. However, in HDM S -wheezers they were associated with upregulation of two coexpression modules comprising multiple type 2- and epithelial-associated genes. The first module was interlinked by the hubs EGFR, ERBB2, CDH1 and IL-13. The second module was associated with CDHR3 and mucociliary clearance genes. Our findings provide new insight into the molecular mechanisms operative at baseline in the airway mucosa in atopic asthmatics undergoing natural aeroallergen exposure, and suggest that susceptibility to asthma amongst these subjects involves complex interactions between type 2- and epithelial-associated gene networks, which are not operative in equivalently sensitized/exposed atopic non-asthmatics.